Investigation of Current Accounts of Islamic Banks: An Islamic Perspective - Muhammad Wasie Fasih Butt (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Islamic banking was engineered to frame a financial model based on contemporary Islamic modes of business and finance. One of the products of Islamic banking is a current account, whose roots and fruits, both are still controversial. Islamic Researchers hold three different opinions regarding fiqh (jurisprudential) status of the current account while the benefits offered by this account have also been the focus of research these days, being regarded by some Islamic scholars as permitted while by others as interest. This conceptual paper aims at exploring the real Islamic basis for these accounts, thus framing the guidelines for its practical applications. Both descriptive and applied research approaches are used to study the relevant literature and current banking practices as well. The general findings show that the nature of this account is that of loan so that its specific injunctions should be applied to all services of this account.